Multiple sclerosis and cancers in Croatia : a possible protective role of the »Mediterranean diet« - Materljan, Eris (Array, 2009)
Abstract: Multiple sclerosis (MS) is an autoimmune disease triggered by a combination of genetic and environmental risk factors which are however individually insufficient to provoke the disease. Previous investigations studied the coexistence of cancer in MS patients, and only a few relations between the geographic distribution of MS and that of cancer. The aim of this research was to find an environmental link between the aetiology of MS and cancers in Croatia. Incidence and prevalence of MS in Croatia were compared with the incidence of the most frequent cancer sites: stomach cancer, cancer of the colon and the rectum, pancreatic cancer, lung cancer, cancer of the kidneys and brain cancer. Data for MS were collected from seven population-based epidemiologic studies which used Poser’ s diagnostic criteria and reported the number of cases and the magnitude of the studied population. Data for cancers were drawn from the Croatian National Cancer Registry.